Past food for thought: the potential of archaeology - Stockhammer, Philipp (Gastronomica, 2016)
Until recently, archaeologists have routinely connected a particular object with a certain function and meaning—especially with regard to eating and drinking practices—and have underestimated the transformative power of intercultural encounters. In my article, I explore the dynamic relationship between food “stuffs” and the objects and practices connected with their consumption. Adopting a transcultural perspective, I want to focus on the changeability of the relation between food “stuffs,” objects, and practices and individual objects’ biographies of usage. I will illustrate my methodological approach with case studies from the late second millennium BCE Eastern Mediterranean where objects for food consumption were widely distributed—and have thus far been interpreted as evidence for the spread of certain practices of consumption over the whole region. By analyzing regional processes of appropriation of these objects I will shed light on the astonishing transformations of their functions and meanings.